Preparation method and application of alpha-MnO2 nanorod and MIL-53 (Al) nanoparticle composite material
By introducing MIL-53(Al) nanoparticles into α-MnO2 to form composite materials, the volume expansion and low ionic conductivity problems of α-MnO2 in aqueous zinc ion batteries were solved, and the capacity and stability were significantly improved.
Patent Information
- Application Number
- CN202411810943.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
α-MnO2 faces volume expansion and low ionic conductivity problems in aqueous zinc ion batteries, which affects its battery capacity and stability.
Hydrothermal in situ growth method was used to prepare composite materials of α-MnO2 nanorods and MIL-53(Al) nanoparticle. The ionic/electronic conductivity of α-MnO2 is improved through the porous structure of MIL-53(Al), and the volume expansion of α-MnO2 is prevented through its stability.
The battery capacity and stability of α-MnO2 in aqueous zinc ion batteries is significantly improved, its ionic conductivity is enhanced, and volume expansion is reduced.
Smart Images

Figure CN119725796A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to battery material technology, and in particular to a technology for improving and enhancing the capacity and stability of α-MnO2 in aqueous zinc ion batteries. 2 Preparation method and application of nanorod and MIL-53 (Al) nanoparticle composite material. Background Art
[0002] Manganese dioxide (α-MnO 2 ) plays an extremely important role in the positive electrode material of aqueous zinc-ion batteries, but it faces multiple challenges, such as volume expansion and low ionic conductivity during charging and discharging. Coating is one of the effective methods to enhance and improve its electrochemical performance. Therefore, the selection and structure of the coating plays a key role in the specific capacity and stability of manganese dioxide. 2 Composite materials have been studied and have indeed improved α-MnO 2 defects. Summary of the invention
[0003] The purpose of the present invention is to provide an α-MnO 2 Preparation method and application of nanorod and MIL-53 (Al) nanoparticle composite material. The composite prepared by this method is referred to as α-MnO 2 @MIL-53(Al), α-MnO prepared by this method 2 @MIL-53(Al) can improve α-MnO 2 Battery capacity and stability in aqueous zinc-ion battery applications.
[0004] The technical solution for achieving the purpose of the present invention is:
[0005] A kind of α-MnO 2 The preparation method of the composite material of nanorods and MIL-53 (Al) nanoparticles comprises the following steps:
[0006] 1) α-MnO 2 Synthesis: 1.5mmol potassium permanganate KMnO 4 30 ml of deionized water was added, ultrasonic treatment was performed for 10 minutes, and then 0.5 ml of hydrochloric acid was added. The mixture was hydrothermally treated in a reactor at 140 ° C for 4 hours. After cooling, the mixture was filtered and the filter cake was washed with deionized water and anhydrous ethanol. Finally, the filter cake was vacuum dried at 70 ° C for 12 hours to obtain α-MnO 2 ;
[0007] 2) Synthesis of functionalized MIL-53(Al): 0.5625 gAl(NO3 ) 3 9H 2 O was dissolved in 10 ml of deionized water and stirred for 10 minutes to form solution A; 0.28 g of terephthalic acid was dissolved in 40 ml of DMF and stirred for 10 minutes to form solution B, then solution B was added to solution A and ultrasonically treated for 30 minutes, and hydrothermally treated in a reactor at 150°C for 24 hours, and then filtered after cooling, and the filter cake was washed with deionized water and methanol, and finally the filter cake was dried at 90°C to obtain gray-white MIL-53 (Al), MIL-53 (Al) and an equal mass of PVP were dissolved in 30 ml of deionized water and stirred for 3 hours, and the sample was centrifuged with deionized water and ethanol to obtain the sample and dried at 70°C for 12 hours;
[0008] 3) α-MnO 2 @Synthesis of MIL-53(Al): 0.0069 g of functionalized MIL-53(Al) was dissolved in 30 ml of deionized water, treated with ultrasound for 15 min, and 1.5 mmol of potassium permanganate KMnO was added. 4 , ultrasonic treatment for 10 minutes, then add 0.5 ml of hydrochloric acid, hydrothermally treat in a reactor at 140 ° C for 4 hours, filter after cooling, and wash the filter cake with deionized water and anhydrous ethanol, and finally vacuum dry the filter cake at 70 ° C for 12 hours to obtain α-MnO 2 Nanorods and MIL-53(Al) nanoparticles composite α-MnO 2 @MIL-53(Al).
[0009] α-MnO prepared by the above preparation method 2 Nanorods and MIL-53(Al) nanoparticles composite α-MnO 2 @Application of MIL-53(Al) in CR2032 button battery.
[0010] In this technical solution, α-MnO is prepared by a hydrothermal in-situ growth method. 2 The composite material composed of nanorods and MIL-53(Al) nanoparticles, on the one hand, the porous and large porosity MIL-53(Al) provides more active sites for ions or electrons, thus improving the 2 On the other hand, MIL-53(Al) has good stability and can stabilize α-MnO 2 morphology to avoid volume expansion during charging and discharging.
[0011] The composite prepared by this method is referred to as α-MnO 2 @MIL-53(Al), α-MnO prepared by this method 2 @MIL-53(Al) can improve α-MnO2 Battery capacity and stability in aqueous zinc-ion battery applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is α-MnO in the embodiment 2 , MIL-53(Al) and α-MnO 2 @MIL-53(Al) XRD and FTIR spectra, where Figure 1 a is α-MnO 2 , MIL-53(Al) and α-MnO 2 @XRD pattern of MIL-53(Al), Figure 1 b is α-MnO 2 , MIL-53(Al) and α-MnO 2 @FTIR graph of MIL-53(Al);
[0013] Figure 2 In the embodiment, α-MnO 2 , MIL-53(Al) and α-MnO 2 @SEM and TEM images of MIL-53(Al), where: Figure 2 a is α-MnO 2 SEM images of Figure 2 b is α-MnO 2 TEM images of Figure 2 c is Figure 2 b is α-MnO 2 A partial enlarged picture of the TEM. Figure 2 d is the SEM image of MIL-53(Al), Figure 2 e is α-MnO 2 @TEM image of MIL-53(Al), Figure 2 f is α-MnO 2 @A partial magnified image of the TEM of MIL-53(Al);
[0014] Figure 3 In the embodiment, α-MnO 2 XPS spectrum and thermogravimetric diagram of @MIL-53(Al), among which, Figure 3 a is α-MnO 2 @MIL-53(Al) full XPS spectrum, Figure 3 b is α-MnO 2 @The narrow spectrum of C1s fitted in XPS of MIL-53(Al), Figure 3 c is α-MnO 2 @The narrow spectrum of Mn2p fitted in XPS of MIL-53(Al), Figure 3 d is α-MnO2 @The narrow spectrum of Mn3s fitted in XPS of MIL-53(Al), Figure 3 e is α-MnO 2 @The narrow spectrum of O1s fitted in XPS of MIL-53(Al), Figure 3 f is α-MnO 2 and α-MnO 2 @TG diagram of MIL-53(Al) in nitrogen atmosphere;
[0015] Figure 4 In the embodiment, α-MnO 2 and α-MnO 2 @MIL-53(Al) CV graph, GCD graph, scan rate and log function analysis graph of peak current, where: Figure 4 a is α-MnO 2 and α-MnO 2 @MIL-53(Al) at 0.3mVs -1 CV comparison chart under scanning rate, Figure 4 b is α-MnO 2 and α-MnO 2 @MIL-53(Al) at 0.3Ag -1 GCD diagram after 50 cycles, Figure 4 c is α-MnO 2 @MIL-53(Al) at 0.1mVs -1 CV graphs of the first three cycles at the scan rate, Figure 4 d is α-MnO 2 @MIL-53(Al) at 0.1mVs -1 -1mVs -1 CV graph, Figure 4 e is the log function analysis diagram of scan rate and peak current, Figure 4 fα-MnO 2 and α-MnO 2 @EIS comparison chart of MIL-53(Al);
[0016] Figure 5 In the embodiment, α-MnO 2 and α-MnO 2 @MIL-53(Al) capacity cycle diagram and GCD diagram and rate performance diagram at different current densities, among which, Figure 5 a is α-MnO 2 and α-MnO 2 @MIL-53(Al) in 1Ag -1 Capacity cycle diagram under current density, Figure 5 b is α-MnO 2and α-MnO 2 @MIL-53(Al) at 0.3Ag -1 Capacity cycle diagram under current density, Figure 5 c is α-MnO 2 @MIL-53(Al) at 0.3Ag -1 GCD diagram under current density, Figure 5 d is α-MnO 2 @MIL-53(Al) capacity cycle diagram and GCD diagram at different current densities, Figure 5 e is α-MnO 2 @MIL-53(Al) rate performance diagram, Figure 5 f is α-MnO 2 @MIL-53(Al) at 0.1Ag -1 Capacity cycling diagram under current density. DETAILED DESCRIPTION
[0017] The content of the present invention is further described below in conjunction with the drawings and embodiments, but the present invention is not limited thereto.
[0018] Example:
[0019] A kind of α-MnO 2 The preparation method of the composite material of nanorods and MIL-53 (Al) nanoparticles comprises the following steps:
[0020] 1) α-MnO 2 Synthesis: 1.5mmol potassium permanganate KMnO 4 30 ml of deionized water was added, ultrasonic treatment was performed for 10 minutes, and then 0.5 ml of hydrochloric acid was added. The mixture was hydrothermally treated in a reactor at 140 ° C for 4 hours. After cooling, the mixture was filtered and the filter cake was washed with deionized water and anhydrous ethanol. Finally, the filter cake was vacuum dried at 70 ° C for 12 hours to obtain α-MnO 2 ;
[0021] 2) Synthesis of functionalized MIL-53(Al): 0.5625 gAl(NO 3 ) 3 9H 2O was dissolved in 10 ml of deionized water and stirred for 10 minutes to form solution A; 0.28 g of terephthalic acid was dissolved in 40 ml of DMF and stirred for 10 minutes to form solution B, then solution B was added to solution A and ultrasonically treated for 30 minutes, and hydrothermally treated in a reactor at 150°C for 24 hours, and then filtered after cooling, and the filter cake was washed with deionized water and methanol, and finally the filter cake was dried at 90°C to obtain gray-white MIL-53 (Al), MIL-53 (Al) and an equal mass of PVP were dissolved in 30 ml of deionized water and stirred for 3 hours, and the sample was centrifuged with deionized water and ethanol to obtain the sample and dried at 70°C for 12 hours;
[0022] 3) α-MnO 2 @Synthesis of MIL-53(Al): 0.0069 g of functionalized MIL-53(Al) was dissolved in 30 ml of deionized water, treated with ultrasound for 15 min, and 1.5 mmol of potassium permanganate KMnO was added. 4 , ultrasonic treatment for 10 minutes, then add 0.5 ml of hydrochloric acid, hydrothermally treat in a reactor at 140 ° C for 4 hours, filter after cooling, and wash the filter cake with deionized water and anhydrous ethanol, and finally vacuum dry the filter cake at 70 ° C for 12 hours to obtain α-MnO 2 Nanorods and MIL-53(Al) nanoparticles composite α-MnO 2 @MIL-53(Al).
[0023] α-MnO prepared by the above preparation method 2 Nanorods and MIL-53(Al) nanoparticles composite α-MnO 2 @Application of MIL-53(Al) in CR2032 button battery.
[0024] In this case, α-MnO was prepared by hydrothermal in situ growth method. 2 The composite material of @MIL-53(Al) was prepared and the crystal structure of the synthesized material was studied by XRD. The morphology of the sample was analyzed by SEM and TEM. The chemical composition and valence state were studied by X-ray photoelectron spectroscopy (XPS). The bonding structure and functional group information of the sample were analyzed by FTIR spectroscopy. The thermogravimetric (TG) curve of the sample was obtained by thermogravimetric analyzer. 2 @MIL-53(Al) composite materials were characterized by structural functional groups and thermal stability;
[0025] Composite material α-MnO 2 @MIL-53(Al) was tested for electrochemical performance using CR2032 button cells: electrode formulation, composed of composite α-MnO 2@MIL-53 (Al), acetylene black and polyvinylidene fluoride binder (PVDF) were mixed with 1 ml of NMP in a mass ratio of 7:2:1 to form a uniform slurry, which was evenly coated on a stainless steel platinum with a diameter of 12 mm and a thickness of 0.1 mm to form an electrode; α-MnO 2 @MIL-53(Al) has an effective mass of about 0.8 mg cm-3 loaded on the current collector -2 , the electrolyte contains 2M ZnSO 4 and 0.1M MnSO 4 The electrochemical tests were carried out in the voltage range of 0.8V to 1.8V using CT-4008Tn, including constant current charge and discharge (GCD) and rate performance charge and discharge tests. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed on a CHI660D electrochemical workstation to characterize the performance of the composite material compared to α-MnO 2 Comparison of electrochemical properties such as capacity and stability.
[0026] Through electrochemical performance testing, it was found that α-MnO 2 @MIL-53(Al) electrode material has better capacity and stability in aqueous zinc-ion batteries than α-MnO alone 2 Electrode materials have been significantly improved:
[0027] like Figure 1 (a) shows α-MnO 2 , MIL-53(Al) and α-MnO 2 @MIL-53(Al) XRD comparison of the three, MIL-53(Al) shows a higher crystallinity and purity. The four main characteristic peaks of MIL-53(Al) are 2θ=9.20°, 10.01°, 15.62° and 18.72°, representing the (101), (200), (011) and (211) crystal planes of MIL-53(Al), which is consistent with the previously reported data. 2 The diffraction peaks of α-MnO 2 Standard card (PDF#44-0141) one-to-one alignment of α-MnO 2 The characteristic peaks 2θ=12.78°, 18.10°, 28.84°, 37.52°, 41.96°, 49.86°, and 60.27° represent α-MnO 2 (110), (200), (310), (211), (301), (411), and (521) crystal planes, indicating that a relatively high purity α-MnO 2 ,α-MnO 2 @MIL-53(Al) diffraction peaks are mainly related to α-MnO2 The characteristic peaks are consistent, and the diffraction peak of MIL-53(Al) at 2θ=9.20° appears, indicating that this method successfully synthesized α-MnO 2 @MIL-53(Al);
[0028] In order to study the functional groups and bonding structure of the samples, infrared spectroscopy was used, such as Figure 1 As shown in (b), in the spectrum of MIL-53(Al), 1509cm -1 and 1603cm -1 The two peaks at 1416 cm -1 The peak at 3421 cm is related to the symmetric stretching vibration of the COO group, while the peak at 3421 cm -1 The broad peak at 755 cm -1 The peak at is identified as the bending vibration of the CH of the benzene ring. 2 In the spectrum, 1371cm -1 The peak at 524 cm is attributed to the vibration of O-Mn-O. -1 The peak at represents the bending vibration of Mn-O in the manganese oxide octahedron. 2 @In the spectrum of MIL-53(Al), α-MnO was found 2 @MIL-53(Al) and α-MnO 2 The spectrum agrees well and at 755cm -1 The bending vibration of CH of the benzene ring appeared, indicating that α-MnO was successfully prepared. 2 @MIL-53(Al);
[0029] like Figure 2 (a) shows α-MnO 2 SEM morphology of the nanorods, the length of which is about 200 nm, α-MnO 2 The diameter is 10-30nm, the surface of the nanorod crystal is smooth and has good crystallinity; Figure 2 (b) shows the α-MnO prepared separately. 2 TEM morphology of nanorods. Figure 2 (c) is α-MnO 2 TEM partial picture of α-MnO 2 The crystal spacing d of the crystal plane is 1.354nm, which represents the 2 (5 4 1) crystal plane; Figure 2 (d) shows the SEM morphology of MIL-53 (Al) prepared separately, showing the shuttle-shaped flake-like uniform particle composition, the crystal surface of the particles is smooth, and the particle size is about 20 nm; Figure 2(e) shows α-MnO 2 @α-MnO in MIL-53(Al) 2 The TEM composite morphology shows that α-MnO 2 The surface of the nanorods is attached with shuttle-shaped MIL-53(Al) nanoparticles. Figure 2 (f) is α-MnO 2 @Partial image of MIL-53(Al) composite, showing that the crystal spacing d of the MIL-53(Al) crystal plane is 0.347nm, representing the MIL-53(Al)(0 2 0) crystal plane; α-MnO in the composite 2 The structure and size of α-MnO did not change much, indicating that this method successfully prepared α-MnO 2 @MIL-53(Al);
[0030] XPS was used to characterize the 2 @MIL-53(Al) composite material element composition and chemical valence analysis: Figure 3 As shown in (a), the full spectrum shows different peaks of C1s, O1s, Mn2p, Mn3s, and Al2p, indicating the presence of C, O, Mn, and Al elements; Figure 3 (b) shows three different peaks in the C1s orbital at 289.13 eV, 285.03 eV, and 284.81 eV, corresponding to -COOH, CC, and benzene ring, respectively; Figure 3 In (c), the two peaks at 642.08 eV and 653.53 eV correspond to Mn2p 3 / 2 and Mn2p 1 / 2 orbitals, respectively, with a spin separation energy of 11.45 eV, confirming that Mn is Mn 4+ exists in the form of α-MnO 2 The average oxidation state (AOS) of Mn in MIL-53(Al) is based on the difference in binding energy between the two peaks of Mn3s (ΔE s ) calculated, such as Figure 3 (d) shows that the formula is AOS = 8.95-1.13ΔE s , the average oxidation state of Mn is 3.03. Figure 3 In (e), the O1s orbital shows two important peaks at 529.65 eV and 531.78 eV, corresponding to Mn-O-Mn and Mn-OC, respectively. The Mn-OC bond indicates that α-MnO 2 @The existence of Mn-OC bonds on the MIL-53(Al) interface indicates that α-MnO 2 There is an interactive bond between α-MnO and MIL-53(Al), which indicates that 2and MIL-53(Al) show strong interactions rather than simple physical mixtures. 2 @The thermal stability of MIL-53(Al) was tested by typical TG in nitrogen atmosphere: Figure 3 As shown in (f), α-MnO 2 When the temperature rises from room temperature to 800℃, the mass loss is small (about 10wt%). 2 @MIL-53(Al) exhibits a multi-stage mass loss, which is attributed to the vaporization of organic ligands in MIL-53(Al) at different temperatures. A slight mass loss occurs at 100°C, which may be due to the volatilization of water vapor. The flash point of terephthalic acid is between 200 and 300°C. 2 @MIL-53(Al) mass loss in this temperature range may be due to the release of free terephthalic acid in MIL-53(Al). When the temperature is between 420 and 520℃, α-MnO 2 @MIL-53(Al) mass loss again indicates that the MIL-53(Al) frame is decomposing, which is consistent with existing reports on MIL-53(Al);
[0031] like Figure 4 (a) shows that at a scan rate of 0.3 mv s -1 When, α-MnO 2 CV curves of @MIL-53(Al) electrode and α-MnO 2 The CV curves of the electrodes are similar, indicating that they have similar redox behaviors. The two redox peaks correspond to H + and Zn 2+ Insertion and extraction, according to the CV curve, α-MnO 2 @MIL-53(Al) electrode material H + The insertion and extraction of α-MnO 2 @MIL-53(Al) electrode voltage difference is 250mV, Zn 2+ The insertion and extraction of α-MnO correspond to the positions of 1.58 V and 1.24 V, respectively, with a voltage difference of 340 mV. 2 Electrode Material H + The insertion and extraction of α-MnO 2 @MIL-53(Al) electrode voltage difference is 290mV, Zn 2+ The insertion and extraction of α-MnO 2 The electrode voltage difference is 390mV, and it is found that α-MnO 2After being compounded with MIL-53(Al), H + and Zn 2+ The voltage interpolation of both insertion and extraction decreased, indicating that α-MnO 2 @MIL-53(Al) electrode has a higher redox reaction rate, and the voltage difference is also related to the charge-discharge voltage platform of the GCD curve. It is worth noting that α-MnO 2 @MIL-53(Al) CV curve compared with α-MnO 2 The CV curve of α-MnO has a larger area, indicating that 2 @MIL-53(Al) has a larger capacity and can store more electrical energy. In the oxidation curve, α-MnO 2 and α-MnO 2 @MIL-53(Al) has two different oxidation peaks. Similarly, two different oxidation peaks are observed in the reduction curve. Although their sites are similar, α-MnO 2 @MIL-53(Al) has a larger current response, and these different peaks correspond to different ion storage, indicating that α-MnO 2 The electrode material coated with MIL-53(Al) promoted the H + and Zn 2+ This may be attributed to the reduction of α-MnO by the composite of MIL-53(Al). 2 Secondly, MIL-53(Al) has abundant porosity and specific surface area, which helps to enhance the H + and Zn 2+ Insertion and extraction;
[0032] like Figure 4 (b) shows α-MnO 2 and α-MnO 2 @MIL-53(Al) at 0.3Ag -1 The image of the 50th cycle of the GCD curve under the current density of , from the image we can see that both have 2 charging and discharging platforms, which is consistent with Figure 4 (a) There are two oxidation peaks and reduction peaks in the CV cycle image, and the charge and discharge platform voltage is consistent with the voltage corresponding to the oxidation peak and the reduction peak. 2 @MIL-53(Al) has a significantly lower voltage difference in charge and discharge platforms than α-MnO 2 The voltage difference means that α-MnO 2 @MIL-53(Al) vs. α-MnO 2 It is more likely to undergo redox reactions, and after 50 cycles, α-MnO 2@MIL-53(Al) has a specific capacity of 256.8 mAhg -1 , significantly higher than α-MnO 2 The specific capacity is 150.8 mAhg -1 ;
[0033] like Figure 4 As shown in (d), in order to understand the mechanism of the electrode electrochemical performance, α-MnO 2 @MIL-53(Al) electrode at 0.1-1mv s -1 CV curves recorded at different scan rates. It is worth noting that with the increase of scan rate, the area of CV curve is constantly increasing, and the shape of the curve remains consistent. The two oxidation peaks and two reduction peaks of the curve are marked as Peak1-Peak4 respectively. Analysis of CV data at different scan rates can provide a deep understanding of the electrode storage mechanism, as shown in the following formula: i = av b ,The measured peak current (i) and scan rate (v) follow a power exponential relationship, where a and b are both adjustable parameters, and the value of b is determined by the slope of the log(i) and log(v) curves, as shown below: log(i) = log(a) + blog(v), where the value of the coefficient b varies in the range of 0-1, with two well-defined conditions, b = 0.5 and b = 1.0, where a b value of 0.5 indicates a diffusion-controlled insertion process, and a b value of 1 indicates a surface pseudocapacitance process. In Figure e, the log(i) and log(v) curves of the two oxidation peaks Peak1 and Peak2 and the two reduction peaks Peak3 and Peak4 are fitted, where Peak1 and Peak4 represent the Zn 2+ Peak2 and Peak3 represent the insertion and extraction of H + The insertion and extraction of Peak1 and Peak4 revealed that the b values were 0.45 and 0.48, respectively, indicating that Zn 2+ The insertion and extraction of Zn are mainly controlled by diffusion. The b values of Peak2 and Peak3 are 0.55 and 0.77, respectively, indicating that Zn 2+ The insertion and extraction of is subject to diffusion-controlled processes and pseudo-capacitance effects;
[0034] like Figure 4 (f) shows α-MnO 2 and α-MnO 2 The fitting curve of the electrochemical impedance spectroscopy (EIS) test of the MIL-53 (Al) electrode has a semicircular pattern in the high-frequency region and a tilted straight line in the low-frequency region, indicating that the electrochemical behavior is mainly controlled by the charge transfer and ion diffusion processes. The equivalent circuit diagram is shown in Figure 4 As shown in the inset of (f), it is worth noting that after fitting, it is found that α-MnO 2@MIL-53(Al)(496.6Ω) is better than α-MnO 2 R ct (549.5Ω) is smaller, indicating that the nanorod-shaped α-MnO 2 The composite of MIL-53(Al) on the surface reduces the charge transfer resistance at the electrode / electrolyte interface, promotes electron transfer and facilitates ion diffusion;
[0035] like Figure 5 (a) shows that the battery is 1Ag -1 At high current density, α-MnO 2 After 1500 cycles of charge and discharge, the specific capacity reaches 35 mAh g -1 , while α-MnO 2 @MIL-53(Al) has a specific capacity of 73.3mAhg after 1500 charge and discharge cycles -1 , and after 250 cycles, the specific capacity remains basically unchanged, which shows that it has good long-cycle stability. Secondly, the coulombic efficiency of both is basically maintained at 100%, such as Figure 5 (b) shows that the battery is at 0.3Ag -1 At a current density of 2 @MIL-53(Al) exhibits impressive capacity density and cycling stability, α-MnO 2 After 170 cycles of charge and discharge, the specific capacity increased from the initial 257 mAh g -1 Decay to 130.8mAhg -1 , the capacity retention rate is 50.9%, while α-MnO 2 @MIL-53(Al) has a capacity of 299.9mAhg after 170 cycles of charge and discharge. -1 Decay to 254mAhg -1 ,The capacity retention rate is 84.7%, which shows that the latter has better capacity stability. Secondly, the charge specific capacity curve and the discharge specific capacity curve basically overlap, indicating that the charge and discharge coulomb efficiency of the two is close to 100%;
[0036] like Figure 5 (c) shows α-MnO 2 @MIL-53(Al) at 0.3Ag -1 The first three cycles of the charge-discharge curve at a current density of , from which we can see that α-MnO 2 @MIL-53(Al) has two charging and discharging platforms during the charging and discharging process. The discharge platform is about 1.4V and 1.3V, and the charging platform is 1.52V and 1.58V, which is also consistent with α-MnO 2@MIL-53(Al) has two redox peaks in its CV image, and the voltages corresponding to the redox peaks are consistent. 2 @MIL-53(Al) in the first round, α-MnO 2 @MIL-53(Al) specific capacity is 300.2mAhg -1 In the third cycle, its specific capacity is 256.0 mAh g -1 , and with the increase of the number of cycles, the potential difference between the charge and discharge platforms has a significant decrease, which indicates that in the first cycle, the electrode has been activated. With the progress of this activation phenomenon, the electrode polarization has a significant decrease, and the discharge voltage platform has increased significantly, as shown in Figure d, which is α-MnO 2 @MIL-53 (Al) rate performance corresponding charge and discharge curves, it is obvious that there are two charge and discharge platforms (region 1 and region 2), as the current density increases from 0.1Ag -1 Increase to 1Ag -1 , the voltage and capacity of the first discharge platform (region 1) gradually decrease, and the voltage and capacity of the second discharge platform (region 2) decrease rapidly. This result indicates that there are different ion embedding mechanisms in these two platforms;
[0037] like Figure 5 (e) shows that the battery is at 0.3Ag -1 , 0.5Ag -1 , 1Ag -1 , 0.5Ag -1 , 0.3Ag -1 At different current densities, the charge and discharge cycles were repeated 8 times. 2 The specific capacity is 252.0 mAh g -1 、208.4mAhg -1 、114.6mAhg -1 、135.1mAhg -1 、158.2mAhg -1 ; And α-MnO 2 @MIL-53(Al) has a specific capacity of 335.6 mAhg -1 、310.5mAhg -1 、269.5mAhg -1 、286.4mAhg -1 、316.6mAhg -1 α-MnO 2 At 0.3Ag -1 At a current density of 252.0 mAh g -1 After 32 cycles, it decays to 158.2 mAh g-1 The capacity retention rate is 62.8% and has experienced significant attenuation. In contrast, α-MnO 2 @MIL-53(Al) at 0.3Ag -1 At a current density of 2.5 %, the specific capacity increased from 335.6 mAh g -1 After 32 cycles, it decays to 316.6 mAh g -1 , the capacity retention rate is 94.3%, as shown in Figure f, at 0.1Ag -1 At a current density of 2 @MIL-53(Al) has a higher specific capacity than α-MnO 2 , and α-MnO 2 @The specific capacity of MIL-53(Al) first increased and then decreased, reaching a maximum of 521.7 mAhg at 31 cycles. -1 Therefore, MIL-53(Al) contributes to the 2 Stability and improvement of α-MnO 2 The role of specific capacity can be attributed to the high specific surface area, abundant active sites and large number of pores of MIL-53(Al), which are beneficial to the diffusion of zinc ions and prevent the α-MnO 2 The dissolution and volume expansion problems during charge and discharge, therefore, these synergistic effects help to enhance and improve the performance of α-MnO 2 specific capacity and long cycle stability.
Claims
1. A method for preparing a composite material of α-MnO2 nanorods and MIL-53 (Al) nanoparticles, characterized in that: The steps include: 1) Synthesis of α-MnO2: 1.5mmol potassium permanganate KMnO4 was added to 30ml deionized water, ultrasonically treated for 10 minutes, and then 0.5ml hydrochloric acid was added. The mixture was hydrothermally treated in a reactor at 140°C for 4 hours. After cooling, the mixture was filtered and the filter cake was washed with deionized water and anhydrous ethanol. Finally, the filter cake was vacuum dried at 70°C for 12 hours to obtain α-MnO2. 2) Synthesis of functionalized MIL-53 (Al): 0.5625 g Al (NO3) 39H2O was dissolved in 10 ml deionized water and stirred for 10 minutes to form solution A; 0.28 g terephthalic acid was dissolved in 40 ml DMF and stirred for 10 minutes to form solution B, then solution B was added to solution A and ultrasonically treated for 30 minutes, hydrothermally treated in a reactor at 150 ° C for 24 hours, filtered after cooling, and the filter cake was washed with deionized water and methanol, and finally the filter cake was dried at 90 ° C to obtain gray-white MIL-53 (Al), MIL-53 (Al) and an equal mass of PVP were dissolved in 30 ml deionized water and stirred for 3 hours, and the sample was centrifuged with deionized water and ethanol and dried at 70 ° C for 12 hours; 3) Synthesis of α-MnO2@MIL-53(Al): 0.0069 g of functionalized MIL-53 (Al) was dissolved in 30 ml of deionized water, and ultrasonically treated for 15 minutes. 1.5 mmol of potassium permanganate KMnO4 was added, and ultrasonically treated for 10 minutes. Then 0.5 ml of hydrochloric acid was added, and hydrothermally treated in a reactor at 140°C for 4 hours. After cooling, the mixture was filtered and the filter cake was washed with deionized water and anhydrous ethanol. Finally, the filter cake was vacuum dried at 70°C for 12 hours to obtain the composite material α-MnO2@MIL-53(Al).
2. Application of the composite material α-MnO2@MIL-53(Al) prepared by the preparation method as described in claim 1 in CR2032 button batteries.